2015
DOI: 10.1080/21645515.2015.1082693
|View full text |Cite
|
Sign up to set email alerts
|

Booster dose after 10 years is recommended following 17DD-YF primary vaccination

Abstract: A single vaccination of Yellow Fever vaccines is believed to confer life-long protection. In this study, results of vaccinees who received a single dose of 17DD-YF immunization followed over 10 y challenge this premise. YF-neutralizing antibodies, subsets of memory T and B cells as well as cytokine-producing lymphocytes were evaluated in groups of adults before (NVday0) and after (PVday30-45, PVyear1-4, PVyear5-9, PVyear10-11, PVyear12-13) 17DD-YF primary vaccination. YF-neutralizing antibodies decrease signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
1
45
1
1
Order By: Relevance
“…A single dose of the YF vaccine is recommended for lifelong protection [39,40], however, this is still an issue of debate. Studies have demonstrated a significant decreasing or even the complete absence of neutralizing antibody titers, effector memory CD4 + and CD8 + T-cells and classical memory B-cells ten years after primary YF vaccination [41][42][43].…”
Section: Yellow Fever Surveillance and Controlmentioning
confidence: 99%
“…A single dose of the YF vaccine is recommended for lifelong protection [39,40], however, this is still an issue of debate. Studies have demonstrated a significant decreasing or even the complete absence of neutralizing antibody titers, effector memory CD4 + and CD8 + T-cells and classical memory B-cells ten years after primary YF vaccination [41][42][43].…”
Section: Yellow Fever Surveillance and Controlmentioning
confidence: 99%
“…Due to the sudden increase in demand and limited vaccine supply, the decision by the Ministry of Health to administer only one dose of the vaccine, as recommended by the World Health Organization, was provisionally endorsable. Nevertheless, booster doses are necessary to ensure longer protection for all YFV vaccines ( CGSYF 2014 , Campi-Azevedo et al 2016 ). Therefore, the emergency decision to administer only one dose of the vaccine recently taken by the Brazilian Ministry of Health should be re-evaluated as soon as the current sanitary situation normalises and new information on duration of immunity is available.…”
mentioning
confidence: 99%
“…At least two recent studies in Brazil showed that the level of neutralising antibodies decreases dramatically in adults and children eight and four years after primary vaccination, respectively ( Caldas et al 2014 , Campi-Azevedo et al 2016 ). In addition, between 1980 and 2017, 29 cases of severe and frequently fatal sylvatic YF cases were reported in people previously vaccinated in Brazil, not including cases in the most recent epidemic ( PAHO 2016 ).…”
mentioning
confidence: 99%